How The Balanced Scorecard Has Impacted Farmers' Productivity In Bantang Kedis Kintamani - Atmadja, I Made Dwita; Heryanda, Komang Krisna; Mayasari, Ni Made Dwi Ariani (Jurnal Pendidikan Ekonomi Undiksha, 2022)
The purpose of this research is to investigate the impact of the balanced scorecard on the performance of farmers' cropping patterns in the hamlet of Bantang Kedis Kintamani. This is a quantitative study conducted using SPSS version 18.0. Multiple linear regression analysis was utilized to analyze the data in this study. According to the findings of this study, there is a substantial level of financial perspective of 0.000, a significant level of customer perspective of 0.039, and a large level of internal business process perspective of 0.031. The significant level of learning and progress is 0.021. All of the balanced scorecard variables have a lower significance threshold = 0.05, indicating that the hypothesis is accepted, and the R square value in the research model is 0.474, with a coefficient of determination of 47.4%. The independent variable appears to have a 47.4% ability to explain the variance of the variable. This study demonstrates the effect of the balanced scorecard on the performance of farmers' planting patterns in the hamlet of Bentang Kedis Kintamani, proving that the balanced scorecard can be used in agriculture and that it is not limited to manufacturing company.